PEMANFAATAN SUMBER DAYA AIR DAS YEH PENET SEBAGAI AIR IRIGASI DAN AIR BAKU PDAM - Mudiasa, I Made; Sila Dharma, IG. B; Suputra, I Ketut (JURNAL SPEKTRAN; Vol 5 No 1 (2017): Vol. 5, No. 1, Januari 2017, 2017)
Abstract : Tukad Penet is one of the biggest rivers in Bali which is used to support farming and fresh water demand. The increasing of water demand in various sectors such as for irrigation and drink water recently using water from Yeh Penet source shows the over use of its water has caused some conflicts between the use of the water user for irrigation and another use. Therefore, it was needed to review the use of Yeh Penet water to see how big the potential of its water that could be exploited to support the water source demand. The optimal analysis of water usage was carried out in six regional irrigation (DI) used Penet river water such as DI Peneng, DI Kacangan, DI Luwuscarang Sari, DI Penarungan, DI Kapal and DI Munggu . This analysis was based on cropping, planting and water management as well as a maximum water raw demand of the regional company of drinking water (PDAM) in Tabanan and Badung regency. Based on the simulation result, water availability in each irrigation regional ( DI) depended on the cropping and planting. It was needed to provide the planting and rotation system for some irrigation regionals in river fluctuation discharge. The deficit of irrigation water balance occurred in DI Peneng, DI Luwuscarang sari, and DI Kacangan . The optimal use of irrigation water in the third irrigation regional was carried out by using planting stimulation and water management. The water balance analysis result at watershed in the part of downstream Penet watershed showed the availability of water surplus occurred in alternative plan I and II. The water balance analysis showed water availability in alternative plan I of a minimum 0.04 million m 3 and maximum 1.43 million m 3 , whereas in alternative plan II the wasted water availability of a maximum 0.25 million m 3 and a maximum 1.51 million m 3 . The potential development of Penet watershed in alternative plan I was 0.67 million m 3 (0.52 m 3 /sec) and in alternative plan II was 0.76 million m 3 (0.58 m 3 /sec) was not able to support the total water demand in Badung and Tabanan regency. Besides, the water source development of Penet watershed only occurred in downstream part of Yeh Penet river to avoid some conflicts of water utilization in Penet watershed.
Keywords: Optimalitation, development, irrigation area, regional company of drinking water (PDAM)